The effect of service quality on consumer satisfaction at fast food restaurants in denpasar - Astina, I Nyoman Gede; Wirawan, Putu Eka; Ying, Lim Hui; Sadipun, Wilhelmus Venrico; Jnanasara, IGN Aryavikan; Astuti, Putu Cindy Ayudia; Kurniawan, Kadek Indra (Institut Pariwisata dan Bisnis Internasional, 2022)
The culinary industry is a small part of the tourism sector in Indonesia, which still exists during the Covid-19 pandemic. This study aims to analyze the existence of fast food restaurants in Bali, with the focus of the study on the effect of service quality on customer satisfaction. The type of research used in this study is associative research and the variables analyzed in this study are physical evidence, reliability, responsiveness, assurance, empathy and customer satisfaction. This research was conducted at Mie Gacoan Gatot Subroto Restaurant, Central Bali, using a sample population of the restaurant's consumers. The sampling technique used purposive sampling, which amounted to 100 respondents. Based on the results of the F-test, it can be concluded that the dependent variable in the form of consumer satisfaction can be significantly influenced by the independent variables in the form of physical evidence, reliability, responsiveness, assurance and empathy together.